Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1099636218795375
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration and buckling analysis of composite sandwich plates in thermal environment

Abstract: In this work, a first-order discrete layer model is performed to deal with the free vibration and buckling analysis of composite sandwich plates in thermal environment. Owing to considering the effect of rotary inertias and shear deformation, thin-to-moderately thick shells can be analyzed. The differential equations of motion are derived from Hamilton’s principle, and account for the nonlinear variation of the in-plane and transverse displacements through the thickness due to temperature variation. These equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…[34]. It can be concluded from Figure 3 that the results obtained from the present research are so close to those reported by Zhai et al [34] for thermal buckling analysis of sandwich plates.…”
Section: Verification Studysupporting
confidence: 90%
See 2 more Smart Citations
“…[34]. It can be concluded from Figure 3 that the results obtained from the present research are so close to those reported by Zhai et al [34] for thermal buckling analysis of sandwich plates.…”
Section: Verification Studysupporting
confidence: 90%
“…The structure is presumed to be exposed to environment with uninform temperature distribution. The material properties of the core and face sheets are considered as [34] :…”
Section: Verification Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The second comparison involves thermal buckling of a rectangular sandwich plate with soft core and single layer orthotropic face sheets (0 � =Core=0 � ). Zhai et al [16] used an analytical solution for this type of sandwich plate with only simply supported boundary conditions. The material properties of the core and face sheets are assumed as follows:…”
Section: Presentmentioning
confidence: 99%
“…It was also concluded that it is possible to maintain the fundamental natural frequency of the structure at a constant value under any operating temperature by implementing an appropriate stable gain control voltage. Zhai et al [16] focused on the buckling temperature and natural frequencies of sandwich plates with soft core and single-layer face sheets. They presented an analytical solution for buckling and vibration of sandwich plates with simply supported type of boundary conditions under thermal environments and illustrated the influence of geometrical parameters on the behaviour of structure in free vibration and buckling.…”
Section: Introductionmentioning
confidence: 99%